The Effect Of Sales Volatility, Company Size, And Debt Levels On Profit Persistence - Adelia Zulfa Marsanda; Dede Sunaryo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this study is to ascertain how debt levels, firm size, and sales volatility affect partial and simultaneous profit persistence. Companies in the consumer cyclicals category that were listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023 were the subject of this study. Purposive sampling, quantitative methodologies, testing using Eviews 12, data gathering procedures employing secondary data, and samples drawn from a total of 21 firms comprise the research methodology employed in this study. The findings demonstrate that profit persistence is unaffected by sales volatility or business size. However, the amount of debt has a major impact on the longevity of profits. At the same time, profit persistence is positively and significantly impacted by sales volatility, firm size, and debt level.